2021
DOI: 10.1021/acsami.1c04770
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-Made Single-Core PLGA Microbubbles as Acoustic Cavitation Enhancers for Therapeutic Applications

Abstract: Microbubbles (MBs), being gas bubbles encapsulated inside a solid shell, have been investigated extensively in the field of therapeutic ultrasound as acoustic cavitation enhancers. Hard-shell MBs have an advantage over soft-shell MBs due to their improved stability. Poly­(lactic-co-glycolic acid) (PLGA) is one of the most attractive polymers for hard-shell MB synthesis; however, very little is known regarding the effect of synthesis parameters on the acoustic cavitation activity of PLGA MBs and the tunability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The treatment settings was shown in Additional file 1: Figure S9. Without HIFU irradiation, negligible tumor inhibition effect could be found in the group treated with DLM@PLGA NPs, indicating the good biocompatibility of PLGA-based nanocarriers as previously reported [44,45]. As shown in Additional file 1: Figure S10, an in vivo imaging system (IVIS) was further used to examine the distribution of fluorescent Cy5.5@PLGA NPs (which was used as a fluorescent substitution of PLGA-based NPs in this study) in tumor-bearing mice.…”
Section: Resultsmentioning
confidence: 54%
“…The treatment settings was shown in Additional file 1: Figure S9. Without HIFU irradiation, negligible tumor inhibition effect could be found in the group treated with DLM@PLGA NPs, indicating the good biocompatibility of PLGA-based nanocarriers as previously reported [44,45]. As shown in Additional file 1: Figure S10, an in vivo imaging system (IVIS) was further used to examine the distribution of fluorescent Cy5.5@PLGA NPs (which was used as a fluorescent substitution of PLGA-based NPs in this study) in tumor-bearing mice.…”
Section: Resultsmentioning
confidence: 54%
“…To improve the in vivo persistence of microbubbles, Chen et al incorporated poly (lactic-co-glycolic acid) (PLGA) polymer into the lipid shell of microbubbles [41] . Tsirkin et al further showed that the addition of PLGA produced hard shell microbubbles with high stability in circulation and an extended cavitation time (approximately 2-fold) [42] .…”
Section: Advanced Basics Of Ultrasound-driven Cavitationmentioning
confidence: 99%
“…The application of FUS primarily causes breakdown of the soft inner dextran phase while also causing some breakdown of the stiff outer PEGDA phase. Compared to microbubbles (which are typically several microns in diameter [2i, 5, 19] ), these biphasic microcapsules can carry large payloads and be used for pulsatile payload release over days. An overview of our process can be seen in Movie S1.…”
Section: Figurementioning
confidence: 99%